Validation of technology in farm trials - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
The principal objective of on-farm trials is to provide feedback to the technology generation/var. improvement process. The trials carried out by CIAT and the Instituto Colombiano Agropecuario on farms in the Colombian regions of Huila, (10 farms in 1980 A), Antioquia (14 farms in 1979 A and 1980 B) and the marginal coffee regions of Restrepo and Darien in the Valle del Cauca (5 and 7 farms in 1980 B, resp.) are described in detail. The bush bean trials with new var. ICA-L-24 and BAT 332 in Huila indicated that a disease resistance strategy to BCMV could increase farmers' yields with or without spraying. Moreover, with the improved maize price and the doubling of maize yields with the new var. Suwan 1, the maize/bean association was much more profitable than any of the other monoculture systems. In the coffee zone the multiple disease resistance of var. BAT 332 was impressive; only this var. responded to fertilization. In Antioquia rapid diffusion of improved control of anthracnose (Colletotrichum lindemuthianum) with benomyl is taking place. Farmers with their local var. Cargamanto can increase yields up to 0.5 kg/ha by using higher densities and artificial support to reinforce maize stalks. The relative performance of new selections with respect to Cargamanto in the farm trials improved substantially from 1979 to 1980; however, the absolute income performance of all new technologies decreased drastically with the abrupt price decline of Cargamanto. Two appendixes are included: (1) detailed description of Phaseolus vulgaris growth habits and (2) a list of CIAT accessions of Phaseolus referred to in this report, including CIAT accession no., identification, local register, and source. (CIAT)